A novel serum m7G-harboring microRNA signature for cancer detection - Chen, Yaxin; Xie, Yufang; Bi, Liyun; Ci, Hang; Li, Weimin; Liu, Dan (Frontiers in Genetics, 2024)
Emerging evidence points to the exceptional importance and value of m 7 G alteration in the diagnosis and prognosis of cancers. Nonetheless, a biomarker for precise screening of various cancer types has not yet been developed based on serum m 7 Gharboring miRNAs. Here, a total of 20,702 serum samples, covering 12 cancer types and consisting of 7,768 cancer samples and 12,934 cancer-free samples, were used for the development and validation of a novel serum m 7 G target miRNA diagnostic signature (m 7 G-miRDS) for cancer detection. The m 7 G-miRDS model, a 12 m 7 G-target-miRNAs signature, demonstrated high accuracy and was qualified for cancer detection. In the training and validation cohort, the area under the curve (AUC) and 95% confidence interval reached 0.974 (0.971 -0.977) and 0.972 (0.969 -0.975), respectively. The m 7 G-miRDS showed superior sensitivity in each cancer type and had a satisfactory AUC in identifying bladder cancer, lung cancer and esophageal cancer. Additionally, the diagnostic performance of m 7 G-miRDS was not interfered by gender, age and benign disease. Our results greatly extended the value of serum circulating miRNAs and m 7 G in cancer detection, and provided a new direction and strategy for the development of novel biomarkers with high accuracy, low cost and less invasiveness for mass cancer screening, such as ncRNA modification.